Pertanian Pisang di Kabupaten Lumajang pada Tahun 1987-2013 - Ade Syalung Maisyah Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Banana cultivation in Kabupaten Lumajang has developed rapidly and has become one of the agricultural commodities with economic value for the community. The geographical conditions of Lumajang Regency, supported by climate, temperature, rainfall, and soil fertility, make this area suitable for banana cultivation. This study aims to determine the development of banana cultivation in Lumajang Regency from 1987–2013 and its impact on the economic life of the community. This research is expected to broaden knowledge regarding the historical development of banana agriculture and serve as a source of information for further studies. The method used in this research is the historical research method, which includes heuristics, source criticism, interpretation, and historiography by utilizing sources such as archives, data from the Central Bureau of Statistics, government documents, journals, books, and interviews. The results show that the development of banana cultivation experienced significant dynamics in terms of production, superior varieties, and cultivation patterns. Banana production increased during the late 1980s to the 1990s, but experienced fluctuations in the 2000s due to the shift of agricultural commodities and several cultivation constraints. The intercropping system implemented by farmers made bananas an additional source of income for the community. In addition, superior varieties such as Mas Kirana bananas were able to increase the economic value of banana commodities and strengthen the identity of Lumajang Regency as the “City of Bananas.” The development of banana cultivation also had an impact on increasing trade activities, creating employment opportunities, and developing home-based banana processing industries.
FINALISASI oleh Arif 2026 Juni 09
Keywords: Keywords : Banana cultivation; Lumajang Regency; Intercroping plant; Farmer groups; Community economy